The influence of vegetation on clays (Thomas Telford, 1984)
The legal aspects of the influence of vegetation on the swelling and shrinking of clays, patterns of soil drying and moisture deficit in the vicinity of trees on clay soils, and evapo-transpiration and heaving clays in South Africa, are just some of the issues discussed in these papers.